Pure and impure tachycardiomiopathy: key differences and long term prognosis. (19th May 2022) - Stronati, G; Urbinati, A; Alfieri, M; Brugiatelli, L; Maiorino, F; Lombardi, G; Barbarossa, A; Ciliberti, G; Compagnucci, P; Casella, M; Dello Russo, A; Guerra, F
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Tachycardiomioathy (TCM) is a reversible cause of left ventricular (LV) dysfunction, secondary to both atrial and ventricular arrhythmias as well as high burden of ectopic beats. Almost 10% of all hospitalizations for acute heart failure (HF) meet the criteria for TCM. TCM is known to frequently recur and therefore cardiovascular related hospitalizations are often needed. While this is true in pure TCM, long term prognosis of impure TCM is still unknown. Purpose: To compare long term prognosis of pure TCM to that of impure TCM in terms of survival rate, time free of recurrence and time free of hospitalizations. Methods: Prospective, observational study enrolling all consecutive patients admitted for de novo acute heart failure, with a confirmed diagnosis of TCM, which was suspected in all patients admitted for heart failure (HF) with a LV ejection fraction <50% and concomitant persistent atrial or ventricular arrhythmia, and confirmed after clinical and echocardiographic recovery. Pure tachycardiomiopathy was defined as an arrhythmia-induced LV dysfunction in an otherwise healthy heart. Impure tachycardiomiopathy was defined as an arrhythmia-mediated TCM, where the arrhythmia may exacerbate an underlying condition and facilitate LV dysfunction. Results: Population included 123 patients with pure TCM and 40 patients with impure TCM. Patients with pure TCM were significantly younger (68±13 vs. 74±10 years; p=0.008) but a with similar risk factor profile and the same prevalence of male gender (63% vs 72%; p=ns). Similarly, echo characteristics did not significantly differ between the two groups, while pure TCM presented a higher HR at admission (124±28 vs. 106±28 bpm; p=0.001) but not at discharge (70±15 vs. 71±14 bpm; p=ns). Pure and impure TCM had similar EF on admission (33±9 vs. 34±7%; p=ns) and time to recovery after the acute event (4.9±0.6 vs. 4.4±1.4 months; p=ns). Pure TCM were more often treated in the acute phase with a rhythm control strategy (81% vs. 67%; p=0.001), mainly electric cardioversion followed by anti-arrhythmic drugs (80% vs. 46%; p<0.001) and AF ablation (16% vs. 3%; p=0.025). Kaplan Meier curves showed that pure TCM present a lower incidence of recurrence (26% vs. 50%; p=0.05; Figure 1) over a 40-month median follow-up. Cumulative incidences of death (24% vs. 30%; p=ns; Figure 2) and thromboembolism (3% vs. 3%; p=ns) were similar between the two groups over the same period. All-cause hospitalizations were similar between the two groups (62% vs. 67%; p=ns) with the impure TCMs experiencing more unplanned hospitalizations for HF recurrences. Conclusions: While pure and impure TCM patients differs in terms of baseline characteristics, they present similar risk of death, thromboembolic events, and hospital admission during a long-term follow-up. Treatment strategy of pure TCM is more often rhythm-oriented and this could explain the lower incidence of HF recurrence.